EFL Teachers’ Belief in Effective Teaching and Their Implementation in Practice - Nisrina, Nisrina; Rahmajanti, Sri; Mukminatien, Nur (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
This is a report on an investigation of the differences between English teachers’ belief in effective teaching and their real practice in remote-area schools in Indonesia. It is assumed that their beliefs play an important role in influencing their decision in the classroom. It also uncovers the possible factors causing the differences. A descriptive study using retrospective method was employed using a questionnaire and an interview to 15 respondents participating in a Teacher Professional Education. The findings indicate that their beliefs about instructional objectives, materials, approach, classroom management, instructional media, and assessment are not always reflected in implementations due to practical reasons or changes of belief either in a positive or negative way.